Producing urban agroecology in the East Bay: from soil health to community empowerment. Issue 5 (27th May 2020) - Siegner, Alana Bowen; Acey, Charisma; Sowerwine, Jennifer
ABSTRACT: Despite a growing civic movement to create spaces for urban agriculture (UA) in U.S. cities, public investment remains both inequitable and inadequate to support the diverse practices and practitioners growing food locally. As a result, outcomes of UA initiatives are uneven, ad hoc, and often the result of resistance and concerted advocacy. This is due, in part, to agriculture not being a standard urban land use designation or central focus of urban policymaking, despite decades of research demonstrating health, food, environmental and educational benefits of growing food in cities. Agroecology is a robust framework for urban food justice advocates and policymakers in the U.S. to identify synergistic ecological, socio-cultural and economic benefits of UA. In this paper, we analyze survey responses from 35 East Bay urban farms through an agroecology lens, documenting how the diverse farms form part of a fragile system that produces important spaces of food, community, health, and culture. With land use and affordability challenges rising in contexts like San Francisco Bay Area, we contend that urban agroecology as both scientific mode of inquiry and set of agricultural practices can improve urban food research-action projects aiming to protect urban farms as vital city infrastructure.